Identification and Antibiogram Studies of Pathogenic Bacteria Isolated From Drinking Water (Unpackaged) In Chittagong City, Bangladesh - Maesha, Afra Nawer; Marzan, Lolo Wal; Akter, Yasmin (Journal of Bangladesh Academy of Sciences, 2018)
Drinking water (unpackaged) samples were collected from twenty roadside shops of different locations in Chittagong metropolitan area, where physicochemical parameters (pH, TDS, temperature) were not exceeded WHO prescribed range in most cases. TVC, TCC, TFCC, TSC, Salmonella spp. and Vibrio spp. were found contaminated as 85%, 70%, 50%, 20%, 30% and 75%, respectively. All the bacterial isolates (n=43) were found positive for 16S rDNA gene, while 12 isolates were coliform positive identified by lacZ gene amplification. Nine bacterial genera were finally identified depending on biochemical characteristics and two of them were further confirmed by 16S rDNA sequencing. Escherichia coli, Citrobacter spp., Klebsiella pneumoniae and Vibrio cholerae were resistant to amoxicillin, where all the bacterial isolates exhibited sensitivity to ciprofloxacin, gentamicin, imipenam and levofloxacin. Presence of human pathogenic and antibiotic resistant bacteria in unpackaged drinking water, suggested for increasing regular monitoring and public awareness to ensure public health safety Journal of Bangladesh Academy of Sciences, Vol. 42, No. 2, 137-153, 2018